(3QSGdI ajeG jcJH HGdVGO hGdXGAs - (3GdgGTej, Gdecj, CHh RcQjG, eMjj GdOjf, jMji Hf YeQ Hf eMeO Hf agO, J (B885(3g`s
(3ChdgG (B:s
(3GdMeO ddg hUdi Gddg Ydi eMeO hBdg(B... (3agPG cJGH ajg eG jcJH HGdVGO hGdXGA (B...(3JCdja(B... (3Hf agO GdgGTej Gdecj(B...s
(3BNQgG (B:s
(3bGd GdQGLQ(B: (3hQeHf HGdChVGa WjGQ GdCab(B. (3JeJ GdQSGdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B8(3, U(B161s
(3eYLe GdeDdajf(B: (3L(B4(3, U(B108s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GddZIs